Dendroclimatic study of a mixed spruce-fir-beech forest in the Czech Republic - Kolář, Tomáš (Les (Ljubljana), 2020)
European forests are undergoing an important transition due to the current climate change, as monocultures are being gradually replaced by mixed forests. Understanding tree growth in mixed forests under a changing climate is challenging because of tree species' adaptation and long-term forest planning. In this study, we evaluate the long-term behaviour of Norway spruce (Picea abies), silver fir (Abies alba) and European beech (Fagus sylvatica) from a low montane range at the Czech-Austrian border. Species-specific tree-ring width chronologies have revealed significantly decreasing growth trends since the 2000s. Temporally unstable climate-growth relationships showed an increasing negative effect of current growing season drought on spruce growth and a positive effect of dormant season tempera-ture on fir and beech growth. Our results suggest that though species% response to climate change differs in the mixed forest, growth reduction in the last years has been proved for all species, likely due to frequent climate extremes.
Keywords: Abies alba; climate change; Fagus sylvatica; Gratzen Mountains; growth trends; kronologije širin branik; mešani gozd; mixed forest; Novohradské hory; Picea abies; podnebne spremembe; tree-ring width chronology; trendi rasti